The Physiochemical Condition of Mangrove Ecosystems in The Coastal District of Sulamo, Kupang, East Nusa Tenggara, Indonesia - Erny Poedjirahajoe; Jeriels Matatula (Institut Pertanian Bogor (IPB University), 2019)
Various rehabilitation and restoration of mangrove forests have been done, but there have not been any significant results. The main reason for the various failures in this activity is that the effort is not based on scientific data such as the suitability of the physicochemical conditions of mangrove habitats along the beach coast of Sulamo District. The purpose of this research is to analyze the condition of salinity, the thickness of mud, and the beach slope of the selected mangrove locations Oeteta, Pariti, Beringin, and Pitai beaches. The salinity conditions show variations, ranging from 19 ppm to 42.33 ppm. The thickness of the mud shows the highest value at 79.11 cm and the slope of mangrove coastal 1–4%. This research shows that the condition of the mangrove ecosystem in the coastal district of Sulamo is still suitable for mangrove growth. This research provides a basic overview of mangrove ecosystem conditions located on the beach coast of the Sulamo district as the basis for planning rehabilitation programs and mangrove restorations in the research area.